2010
DOI: 10.1021/ef900513a
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic and Noncatalytic Mechanisms in Steam Gasification of Char from the Pyrolysis of Biomass

Abstract: Steam gasification of chars from the pyrolysis of a Japanese bamboo and cedar was studied using a reactor that enabled experimental definition of the gas composition in the vicinity of gasifying char particles. Intraparticle diffusion of neither steam nor the product gases influenced the kinetics of gasification. The chars underwent noncatalytic and catalytic gasification in parallel. The noncatalytic gasification, in which kinetic parameters were successfully defined by those for the gasification of the acid-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
110
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(123 citation statements)
references
References 33 publications
5
110
0
Order By: Relevance
“…The chips have an average size of 10  10  2 mm, 50.9 wt.% carbon and 3 -3-wt.% moisture content. The pyrolysis was carried out with a feeding rate, an average residence time, a heating rate, a peak temperature, and a gas pressure inside the reactor of 270 g h −1 , 47 s, 5.0-5.5 C s −1 , 500 C, and 1.0 atm, respectively [2]. The slow pyrolysis produces char, heavy tar, light tar which consist of two separate phases: organic liquid (water-insoluble fraction) and pyroligneous acid (water-soluble fraction), and gaseous products.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chips have an average size of 10  10  2 mm, 50.9 wt.% carbon and 3 -3-wt.% moisture content. The pyrolysis was carried out with a feeding rate, an average residence time, a heating rate, a peak temperature, and a gas pressure inside the reactor of 270 g h −1 , 47 s, 5.0-5.5 C s −1 , 500 C, and 1.0 atm, respectively [2]. The slow pyrolysis produces char, heavy tar, light tar which consist of two separate phases: organic liquid (water-insoluble fraction) and pyroligneous acid (water-soluble fraction), and gaseous products.…”
Section: Methodsmentioning
confidence: 99%
“…Sustainability in energy recovery from biomass such as steam gasification of char is becoming attractive because biomass to energy conversion adds no additional greenhouse gases to the atmosphere [1,2]. The char as highquality solid fuel is produced from pyrolysis and its higher yield can be recovered by slow pyrolysis than fast or flash ones [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In the current investigation, many researchers [13][14][15][16][17][18] found that alkali and alkaline earth metallic species (AAEMs) dispersed in biomass and/or biochar as different chemical speciations, play significant catalytic roles in biochar gasification reactivity, and that AAEMs volatilized as a gaseous phase would also take part in homogeneous reforming reactions [19]. The concentration and dispersion of AAEMs, according to the results obtained by Wu et al [20], is a significant factor affecting the catalytic activity of AAEMs during biomass gasification, which varies constantly due to the carbon consumption and the release/migration of AAEMs [21,22].…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, toxic organic halogen compounds are converted to stable and safe inorganic salts by carbonates, so the gaseous products generated should be halogen-free and can be used as fuel. Gasification in the presence of carbonates had been proposed for coal 17) and other heavy hydrocarbons 18) . The catalytic effect of potassium in coal gasification has also been reported in many previous studies 19) .…”
Section: Steam Gasificationmentioning
confidence: 99%